The Effect of Music Training on Mental Health among High School Students - Duan, Lian; Zheng, Ce (Música Hodie, 2021)
Understanding how music lessons affect mental health allows, among other things, to improve education and therapeutic outcomes. This study of 112 high school students aged 12 to 17 years seeks to determine whether there is a positive correlation between musical activity and the mental state of children. All students underwent two surveys and art therapy session at baseline and at the end of experiment. The results of the study show music training positively correlates with mental health and has a beneficial effect on students’ well-being. The limitations of the study include the small sample size and subjective research method.